2011
DOI: 10.1108/14720701111159262
|View full text |Cite
|
Sign up to set email alerts
|

How relevant is corporate governance and corporate social responsibility in emerging markets?

Abstract: Purpose -The principal aim of this research is to provide an in-depth analysis of existing practices of corporate governance in mature markets and to compare and contrast these approaches with CG and CSR practices in emerging markets, given the growing influence of EMs on the global economy.Design/methodology/approach -The methodology employed in the study is to survey the main theoretical approaches for understanding and CG in relation to mature markets and EMs.Findings -The paper makes a small but important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 50 publications
0
56
0
Order By: Relevance
“…It has been suggested that emerging markets have a tendency to show weaker measures of corporate governance and sustainability (Peters, Miller and Kusyk 2011). However, it is difficult to evaluate the interaction between corporate governance characteristics and the extent of sustainability disclosure in emerging economies since little has been published on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that emerging markets have a tendency to show weaker measures of corporate governance and sustainability (Peters, Miller and Kusyk 2011). However, it is difficult to evaluate the interaction between corporate governance characteristics and the extent of sustainability disclosure in emerging economies since little has been published on this issue.…”
Section: Introductionmentioning
confidence: 99%
“…There is a demand to examine MNCs in emerging markets (Peters et al 2011;Reimann et al 2012), such as MENA and MEA…”
Section: Research Gapsmentioning
confidence: 99%
“…A focus on the East must therefore be considered, plus the developing nations and emerging markets of these regions. It must be acknowledged that a ''one size fits all'' CSR systems based on Western codes and regulations should not necessarily be implemented in the East, or in developing countries or emerging markets (Peters et al 2011).…”
Section: Stakeholder Understanding Of Csr In Emerging Markets 61mentioning
confidence: 99%
“…What one must remember here is that, the very concept of CSR differs between these two economies in terms of its definition as well as implementation. And, there is no comprehensive, "one size fits all" global corporate governance or CSR system, based on western codes and regulations that can be implemented in emerging markets (Peters et al 2011), hence, it is better to limit our study of CSR to the emerging markets alone for a focused approach.…”
Section: Dilemmas and Challenges Of An Emerging Nationindiamentioning
confidence: 99%